2017
DOI: 10.1177/1555412017746305
|View full text |Cite
|
Sign up to set email alerts
|

Word Play: A History of Voice Interaction in Digital Games

Abstract: The use of voice interaction in digital games has a long and varied history of experimentation but has never achieved sustained, widespread success. In this article, we review the history of voice interaction in digital games from a media archaeology perspective. Through detailed examination of publicly available information, we have identified and classified all games that feature some form of voice interaction and have received a public release. Our analysis shows that the use of voice interaction in digital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…Research on voice interaction in videogames has noted social context as an important factor in how the games are played [1,14,17]. An analysis of online responses to voice interaction games found that players preferred voice commands that allowed them to speak in the voice of their character; commands that did not match what the player-character might say were described by players as "uncomfortable" and "embarrassing" [7].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on voice interaction in videogames has noted social context as an important factor in how the games are played [1,14,17]. An analysis of online responses to voice interaction games found that players preferred voice commands that allowed them to speak in the voice of their character; commands that did not match what the player-character might say were described by players as "uncomfortable" and "embarrassing" [7].…”
Section: Related Workmentioning
confidence: 99%
“…Since at least the 1980s, game designers have sought to make voice interaction fun; with some success [1]. Researchers have documented an array of approaches to voice-controlled games, including some that recreate the characterful speechdriven technology of science fiction [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on voice interaction in digital games dates to the '70s [1]. One of the earliest examples of a game prototype augmented with a speech recognition system is VoiceChess supporting standardized chess instructions [24].…”
Section: Related Work 21 Voice Interaction In Gamesmentioning
confidence: 99%
“…Video game companies have integrated voiceactivated services and game mechanics in various recent titles. With the rapid technological improvements in speech recognition and the growing availability of microphones in consumer gaming devices, there is an exciting potential for voice user interfaces in gaming [1].…”
Section: Introductionmentioning
confidence: 99%